2017
DOI: 10.1097/mjt.0000000000000534
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Neurologic and Ophthalmologic Safety of Oral Administration of Tedizolid for Up to 21 Days in Healthy Volunteers

Abstract: Using an extensive battery of ophthalmologic tests and detailed neurologic clinical examination, there was no evidence of clinical or subclinical neurologic or ophthalmologic changes suggestive of peripheral or optic neuropathy in healthy volunteers who received therapeutic and supratherapeutic doses of oral tedizolid for periods of up to 21 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…It is also in line with the suggestion that the selection of tedizolid as clinical candidate was based more on improved intrinsic activity (including against linezolidresistant strains) than safety considerations (24). In phase I studies (with escalating dose and treatment duration up to 21 days), tedizolid was, however, shown to cause less thrombocytopenia (65) and no clinical or subclinical neurologic or ophthalmologic changes (66). Moreover, tedizolid, administered for 9 months to rats at doses up to 8-fold larger than its approved human use did not cause significant neuropathies, which are known to develop with linezolid under these conditions (27).…”
Section: Discussionsupporting
confidence: 70%
“…It is also in line with the suggestion that the selection of tedizolid as clinical candidate was based more on improved intrinsic activity (including against linezolidresistant strains) than safety considerations (24). In phase I studies (with escalating dose and treatment duration up to 21 days), tedizolid was, however, shown to cause less thrombocytopenia (65) and no clinical or subclinical neurologic or ophthalmologic changes (66). Moreover, tedizolid, administered for 9 months to rats at doses up to 8-fold larger than its approved human use did not cause significant neuropathies, which are known to develop with linezolid under these conditions (27).…”
Section: Discussionsupporting
confidence: 70%
“…No cases of lactic acidosis or peripheral or optical neuropathy were described during tedizolid use in our study. In fact, in the study conducted by Fang et al in volunteers receiving different doses of tedizolid for up to 21 days, they found no evidence of neurologic or visual changes (30). Kim et al, in their study of patients receiving tedizolid during a median of 91 days, reported peripheral neuropathy in five patients (20%).…”
Section: Discussionmentioning
confidence: 94%
“…Of note, the reduced inhibitory effect on central nervous system (CNS) monoamine oxidase could be due to the lower CNS penetration of tedizolid compared to linezolid, as observed in rats.52 Whether or not this could also impair the efficacy of tedizolid in some possible off-label indications (eg, CNS infections) deserves further investigation. Finally, no clinically meaningful ophthalmological or neurological alterations were observed in phase I volunteers receiving tedizolid at supratherapeutic doses for 21 days 53…”
Section: Methodsmentioning
confidence: 91%